Modified K-Means Clustering with Semi Grouping Perspective : A Study - Al Afghani, Said; Chandra, Gerry (AI Society & STMIK Indonesia, 2023)
In this note, we will provide some results of a literature study related to one of the clustering methods, namely K-Means, but with some modifications, devoted to the case of computation time. Modifications were made at the time of determining the cluster center by previously applying principal component analysis (PCA), other researchers [4] proposed this method first, which differs in this note, namely in the preprocessing of the data before principal component analysis is carried out. Comparison of the accuracy of the cluster results is also given in this note.